Тексти релігійного стилю як джерело поповнення джерельної бази сучасної української тлумачної лексикографії - Скаб, М. (Лексикографічний бюлетень, 2015)
Нашою метою є обґрунтувати потребу та прокоментувати обсяг залучення текстів релігійного стилю для формування картотеки загальномовного тлумачного словника української мови. The article touches upon the necessity and volumes of texts of religious style which are used in order to form the cataloguefor the generalexplanatorydictionary of the Ukrainian language. The author draws a conclusion that it isabsolutely necessary to include the Bible texts translated by Ohiyenko I., Khomenko I., Turkonyak R. and patriarch Filaret as well as liturgical, patristic, hagiographic, preachy, religious-journalistic, educational-religious, belles-lett res-religious and church-epistolary textsinto the source base of the dictionary.